Comparative epigenetic and genetic spatial structure of the perennial herb Helleborus foetidus: Isolation by environment, isolation by distance, and functional trait divergence. Issue 8 (16th August 2017) - Herrera, Carlos M.; Medrano, Mónica; Bazaga, Pilar
Abstract : PREMISE OF THE STUDY: Epigenetic variation can play a role in local adaptation; thus, there should be associations among epigenetic variation, environmental variation, and functional trait variation across populations. This study examines these relationships in the perennial herb Helleborus foetidus (Ranunculaceae). METHODS: Plants from 10 subpopulations were characterized genetically (AFLP, SSR markers), epigenetically (MSAP markers), and phenotypically (20 functional traits). Habitats were characterized using six environmental variables. Isolation‐by‐distance (IBD) and isolation‐by‐environment (IBE) patterns of genetic and epigenetic divergence were assessed, as was the comparative explanatory value of geographical and environmental distance as predictors of epigenetic, genetic, and functional differentiation. KEY RESULTS: Subpopulations were differentiated genetically, epigenetically, and phenotypically. Genetic differentiation was best explained by geographical distance, while epigenetic differentiation was best explained by environmental distance. Divergence in functional traits was correlated with environmental and epigenetic distances, but not with geographical and genetic distances. CONCLUSIONS: Results are compatible with the hypothesis that epigenetic IBE and functional divergence reflected responses to environmental variation. Spatial analyses simultaneously considering epigenetic, genetic, phenotypic and environmental information provide a useful tool to evaluate the role of environmental features as drivers of natural epigenetic variation between populations.